A Comprehensive Review of Distributed Coding Algorithms for Visual Sensor Network (VSN) - Ebrahim, Mansoor; Chong, Chai Wai (International journal of communication networks and information security, 2014)
Since the invention of low cost camera, it has been widely incorporated into the sensor node in Wireless Sensor Network (WSN) to create the Visual Sensor Network (VSN). Nevertheless, the usage of the camera is bringing with it a lot of new challenges, because all the sensor nodes are powered by batteries. Hence, energy consumption is one of the most critical issues that have to be taken into consideration. In addition to this, the use of batteries has also limited the resources (memory, processor) that can be incorporated into the sensor node. The lifetime of a VSN decreases quickly as the image is transferred to the destination. One of the solutions to the aforementioned problem is to reduce the data to be transferred in the network by using image compression. In this paper, a comprehensive survey and analysis of distributed coding algorithms that can be used to encode images in VSN is provided. The paper also includes an overview of these algorithms, together with their advantages and deficiencies when implemented in VSN. These algorithms are then compared at the end to determine the algorithm that is more suitable for VSN.